Odpowiedzi

  • Użytkownik Zadane
2009-10-18T13:25:26+02:00
(√6 * √12 * √2 - (√15)²) = √6*12*2 - 15 = 12 - 15 = -3
√ - tu będą liczby takie jak : 6, 12, 2

(√18 : √2) * ³√81 : ³√3 + (√0,18 : √2) * √400 = √9 * 3 : ³√3 + 0,3 * 20 =
= √9 : ³√3 * 3 + 6
Najlepsza Odpowiedź!
2009-10-18T13:55:13+02:00
(√6 * √12 * √2 - (√15)²)= (√6 * √12 *√2 - 15)= ("√6 * 12 * 2" - 15)= √144 - 15= 12 - 15= -3

"wszystkie liczby wyliczyc pod jednym pierwiastkiem"


(√18 : √2) * ³√81 : ³√3 + (√0,18 : √2) * √400= √9 *³√27 + √0.09 * √400= 3 * 3 + 0,3 * 20= 9 + 6= 15